Santri Community Construction of Pancen Tradition in Templek Hamlet, Sumberduren Village, Kediri Regency, Indonesia - Pipit Kiptiyah; Novi Fitia Maliha; Siti Marpuah (Journal of Religion, Local Politics, and Law, 2025)
The phenomenon of Pancen tradition in Templek Hamlet, Sumberduren Village, Kediri Regency, is a cultural practice preserved by the santri community as a form of respect for deceased ancestors. This tradition attracts attention because it survives in the midst of a majority Muslim community that is obedient, even though the practice of Pancen itself is not regulated in Islamic teachings. By referring to Peter L. Berger's social construction theory, this study aims to analyze how the people of Templek Hamlet construct and internalize the meaning of Pancen through the processes of externalization, objectification, and internalization. This study also clarifies the role of religious leaders and village elders in strengthening the sustainability of the tradition through social legitimacy and inter-generational learning. The results show that the Pancen tradition has been successfully maintained because it has been internalized as a sacred cultural identity and is seen as in line with local Islamic values. Through social construction, the Pancen tradition is not only a ritual of respect for ancestors but also functions as a social binder that strengthens inter-citizen relations and family ties in the Templek Hamlet community